A maturidade digital na Indústria 4.0: explorando a integração de tecnologias nas dimensões de operações, estratégia corporativa e sustentabilidade na cadeia de suprimentos: uma analise em uma indústria termoplástica no PIM - Pereira, Jennifer Raquel Santos (Brasil, 2025)
This paper investigates the digital transformation of a thermoplastics industry, with an emphasis on the adoption of new technologies in the areas of production, operations, corporate strategy and supply chain sustainability. The research combined an extensive and a detailed case study, using data extracted from the PIMM 4.0 system, which provides information on the company's digital performance. The results reveal that, despite advanced technological advances in production and operations management, there are still gaps that prevent a complete digital upgrade. In particular, the need to to integrate digital solutions more deeply into the supply chain, in addition to strategic management to keep up with the fast pace of Industry 4.0. The study reinforces the importance of more robust digital planning to increase competitiveness and sustainable and sustainable efficiency in the thermoplastics sector.